Guillain Barre Sendromu’nda Optik Nörit - Güngör, Levent; Türker, Hande; Onar, Musa K. (My University, 2007)
Guillain-Barre sendromu (GBS) değişik klinik prezentasyonlarla seyredebilen demiyelinizan bir nöropatidir. Nadiren fulminan bir seyir gösterebilir. GBS’de nadiren optik nörit de bildirilmiştir. Ancak klinik ağır nörolojik tablo içerisinde bu tutulum gözden kaçabilir. Bu yazımızda, tama yakın kilitlenme sendromuna giren fulminan gidişli bir GBS olgusunda, bilateral optik sinir tutulumu bildirilmektedir. Hastanın klinik ve elektrofizyolojik izlemi tartışılmış ve optik sinir tutulumunun gösterilmesinde görsel uyarılmış potansiyellerin önemi vurgulanmıştır.

Guillain-Barre syndrome (GBS) is an acute demyelinating polyneuropathy with so many clinical variations. Sometimes the disease may be fulminant. In rare cases, optic neuritis may be seen. But, because of the severe neurological clinical deficits, this involvement may be overlooked. Here we report a case of GBS with bilateral optic neuritis and near locked-in state. While we summarize the clinical progress and the electrophysiological follow up of the case, we underline the importance of visual evoked potentials (VEP) to show optic nerve involvement.
Optic neuritis in Guillain Barre syndrome
Keywords: Göz Hastalıkları